Tisp40 Induces Tubular Epithelial Cell GSDMD-Mediated Pyroptosis in Renal Ischemia-Reperfusion Injury via NF-κB Signaling - Xiao, Chengcheng; Zhao, Haijun; Zhu, Hai; Zhang, Yingyu; Su, Qiuju; Zhao, Feng; Wang, Renhe (Frontiers in Physiology, 2020)
Renal ischemia-reperfusion injury (IRI) is a major cause of acute kidney injury (AKI). As a transcription factor, Tisp40 has been found to be involved in renal IRI. However, the role of Tisp40 in tubular epithelial cell (TEC) pyroptosis of renal IRI remains unknown. In this study, we investigated the relationship between Tisp40 and GSDMD-mediated pyroptosis induced by ischemia-reperfusion in vivo and oxygen-glucose deprivation/reoxygenation in vitro. Cell viability was evaluated using the CCK-8 assay. Lactate dehydrogenase release was also evaluated. Interleukin (IL)-1β and IL-18 were measured using the enzyme-linked immunosorbent assay and NLRP3 and caspase-1 were measured using quantitative reverse transcription-PCR. Western blotting was performed to detect whether Tisp40 is upregulated or downregulated in TCMK-1 cells. The levels of IL-1, IL-18, NLRP3, and caspase-1 were determined in the kidneys of C57BL/6 or Tisp40 knockout mice. In addition, the role of Tisp40 in GSDMD-mediated pyroptosis of TECs was assessed using flow cytometry in vitro and TUNEL staining in vivo. We found that loss of Tisp40 prevented GSDMD-mediated pyroptosis of TECs by inhibiting NLRP3, caspase-1, IL-1βand IL-18 via a reduced nuclear factor-κB p65 activation. Collectively, our findings provide insight into the mechanism of how Tisp40 regulated GSDMD-mediated pyroptosis in renal IRI.